Germany's Immigration Policy Towards Highly-Skilled Workers in the 21stCentury - N. N. Bolshova (Vestnik MGIMO-Universiteta)
At the end of XX - beginning of XXI century due to accelerating the transition of the world economy to the innovative way of development, "knowledge" has become a direct force of production, significantly increased the role of human capital as the main factor in future economic growth and competitiveness of modern states. In turn, developed and developing countries, faced with a shortage of personnel in high-tech industries and the "brain drain", modernize their immigration policy to attract highly qualified foreign personnel from all over the world and to secure its own intellectual resources. The article examines recent changes in the modern migration policy in Germany, which has become, on the one hand, more selective to different categories of workers, and on the other hand - more open for skilled personnel, especially from developing countries. The purpose of this policy is primarily to cover the shortage of skilled personnel in the national labor market by attracting foreign specialists.